HUBUNGAN KECEMASAN MATEMATIS DAN ADVERSITY QUOTIENT TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS X SMK TI BALI GLOBAL DENPASAR TAHUN PELAJARAN 2019/2020 - I Kadek Yogi Mayudana (LP3M Universitas PGRI Mahadewa Indonesia, 2020)
The purpose of this research is to determine the relationship between mathematical anxiety and adversity quotient on student mathematics learning outcomes. This type of research is correlational and uses the Ex Post Facto method. This research is conducted to examine events that have occurred and then to look back through the data to find the factors and causes that may have occurred for the events under study. In this study, there are two variables, namely two independent variables and one dependent variable. The population in this study was class X SMK TI Bali Global Denpasar in 2019/2020. The technique used was simple random sampling technique, namely by lottery where the class was drawn. The data that has been collected are mathematical anxiety, adversity quotient, and students' mathematics learning outcomes were analyzed using parametric statistics. To test the hypothesis in this study using multiple regression methods. In this study, data analysis will be carried out with the help of the SPSS 22.0 for Windows program. Before performing multiple regression analysis, first a descriptive statistical analysis and prerequisite analysis were carried out. The results of research and data analysis of the relationship between mathematical anxiety and adversity quotient on mathematics learning outcomes of class X students of SMK TI bali Global Denpasar.